Deranged liver among Sudanese Patients with Dengue Virus Infection in Port Sudan Teaching Hospital - Bashir Abdrhman Bashir Mohamed (Sudan Journal of Medical Sciences)
Background Deranged liver is a well-recognized feature of dengue infection, often demonstrated by coagulopathy and mild to moderate increase in transaminase levels although jaundice and fulminant hepatic failure are generally uncommon.